Management of TYLCD Using Non-Woven Row Covers and Acibenzolar-S-Methyl in Greenhouse Tomatoes - Sirigu, A.; Nannini, M.
The effectiveness of alternative strategies for TYLCD management was investigated in two preliminary experiments carried out on tomato commercial crops. In 2005 the effects of four acibenzolar-S-methyl post transplant applications were evaluated. In the second month after planting the trial evidenced a 21-28
Keywords: PLANT ACTIVATOR; SYSTEMIC ACQUIRED RESISTANCE; BION; CONTROL STRATEGIES